Amyloid Beta and Tau Cooperate to Cause Reversible Behavioral and Transcriptional Deficits in a Model of Alzheimer’s Disease - Pickett, Eleanor K.; Herrmann, Abigail G.; McQueen, Jamie; Abt, Kimberly; Dando, Owen; Tulloch, Jane; Jain, Pooja; Dunnett, Sophie; Sohrabi, Sadaf; Fjeldstad, Maria P.; Calkin, Will; Murison, Leo; et al. (Cell reports (Cambridge), 2019)
A key knowledge gap blocking development of effective therapeutics for Alzheimer’s disease (AD) is the lack of understanding of how amyloid beta (Aβ) peptide and pathological forms of the tau protein cooperate in causing disease phenotypes. Within a mouse tau-deficient background, we probed the molecular, cellular, and behavioral disruption triggered by the influence of wild-type human tau on human Aβ-induced pathology. We find that Aβ and tau work cooperatively to cause a hyperactivity behavioral phenotype and to cause downregulation of transcription of genes involved in synaptic function. In both our mouse model and human postmortem tissue, we observe accumulation of pathological tau in synapses, supporting the potential importance of synaptic tau. Importantly, tau reduction in the mice initiated after behavioral deficits emerge corrects behavioral deficits, reduces synaptic tau levels, and substantially reverses transcriptional perturbations, suggesting that lowering synaptic tau levels may be beneficial in AD. [Display omitted] •Aβ and tau work together to cause behavioral and transcriptional deficits in mice•In mice with Aβ and tau, glial gene expression increases and synaptic genes decrease•Tau is present in synaptic terminals in APP/PS1+Tau mice and human Alzheimer brain•In mice, lowering tau levels improves cognition and restores gene expression One of the mysteries of Alzheimer’s disease is how the two key pathological proteins, amyloid beta and tau, interact. Pickett et al. use a mouse model to show that these proteins cooperate to change behavior and gene expression and that these phenotypes recover when tau levels are lowered.